2015
DOI: 10.1063/1.4907252
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of nanostructured topological insulator Bi2Se3

Abstract: To enhance thermoelectric performance by utilizing topological properties of topological insulators has attracted increasing attention. Here, we show that as grain size decreases from microns to ∼80 nm in thickness, the electron mobility μ increases steeply from 12–15 cm2 V−1 s−1 to ∼600 cm2 V−1 s−1, owing to the contribution of increased topologically protected conducting surfaces. Simultaneously, its lattice thermal conductivity is lowered by ∼30%–50% due to enhanced phonon scattering from the increased grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 19 publications
1
33
1
Order By: Relevance
“…[29][30][31] As a result, the TE coefficients of TIs are no longer intrinsic material properties, rather they are significantly influenced by metallic surface states. [29][30][31] Nonetheless, the role of TISS in TE transport still remains controversial, because some researchers reported enhanced ZT values due to the existence of TISS 14,32,33 while other claim the TISS could degrade TE properties, especially when the surface-to-volume ratio (s/v) is very large. 30,31 In this study, we performed a systematic investigation of the influence of TISS on the TE properties by varying the s/v of Bi 2 Se 3 NWs.…”
mentioning
confidence: 99%
“…[29][30][31] As a result, the TE coefficients of TIs are no longer intrinsic material properties, rather they are significantly influenced by metallic surface states. [29][30][31] Nonetheless, the role of TISS in TE transport still remains controversial, because some researchers reported enhanced ZT values due to the existence of TISS 14,32,33 while other claim the TISS could degrade TE properties, especially when the surface-to-volume ratio (s/v) is very large. 30,31 In this study, we performed a systematic investigation of the influence of TISS on the TE properties by varying the s/v of Bi 2 Se 3 NWs.…”
mentioning
confidence: 99%
“…However, they are mostly attributed to suppression of phonon transportation or filtering of low-energy electrons. 7,87 Sun et al 88 found some evidence of the surface contributions through a series of measurements and analysis. The electron mobility µ in Bi 2 Se 3 nanocomposites produced by milling and sintering is found to increase by 50 times at 300 K, when the grain size decreases from microns to~80 nm in thickness.…”
mentioning
confidence: 99%
“…However, the improvement of their properties was achieved due to a decrease of the lattice thermal conductivity. Some papers report an increase in the power factor in nanograined Bi 2 Se 3 or nanosheets of Bi 2 Se 3 . But the effect, observed in nanograined Bi 2 Se 3 hardly has a topological nature, since, for a formation of topological surface states, a grain of TI should be in direct contact with sufficiently thick layer of a trivial insulator, however, no phase other than Bi 2 Se 3 was present in the samples of ref.…”
Section: Thermoelectric Efficiency Of Tismentioning
confidence: 98%
“…But the effect, observed in nanograined Bi 2 Se 3 hardly has a topological nature, since, for a formation of topological surface states, a grain of TI should be in direct contact with sufficiently thick layer of a trivial insulator, however, no phase other than Bi 2 Se 3 was present in the samples of ref. . The power factor of the Bi 2 Se 3 nanosheets in principle can increase due to contribution of the surface states, however, the authors of ref.…”
Section: Thermoelectric Efficiency Of Tismentioning
confidence: 98%
See 1 more Smart Citation